Expression of MMP-9 and VEGF in Meningiomas and Their Correlation with Peritumoral Brain Edema. (3rd March 2015) - Reszec, Joanna; Hermanowicz, Adam; Rutkowski, Robert; Turek, Grzegorz; Mariak, Zenon; Chyczewski, Lech
Abstract : Meningiomas constitute up to 13% of all intracranial tumors. The predictive factors for meningioma have not been unambiguously defined; however some limited data suggest that the expression of matrix metalloproteinases (MMPs) and vascular endothelial growth factor (VEGF) may be associated with the presence of peritumoral brain edema (PTBE) and worse clinical outcome. The aim of this study was to analyze the expressions of MMP-9 and VEGF in a group of meningiomas of various grades and to study associations between these two markers and PTBE. The study included patients with supratentorial meningiomas. The patients were divided into low- (G1) and high-grade meningiomas (G2 and G3). PTBE was assessed on MRI. The expressions of VEGF and MMP-9 were determined immunohistochemically. The expression of MMP-9 was observed significantly more often in G3 meningiomas than in lower grade tumors. The presence of stage II or III PTBE was associated with a significant increase in MMP-9 expression. The expression of VEGF did not differ across the PTBE stages. Our findings point to a significant role of MMP-9 and VEGF in the pathogenesis of peritumoral brain edema in low- and high-grade meningiomas.